EXPORT PERFORMANCE OF GRAPES IN INDIA - A.D. SATHYENDRA KUMAR* and M. DEVARAJ, (The Journal of Research ANGRAU, 2020)
The study(2018-19) focused on the export performance of fresh grapes in India during pre-WTO and post-WTO period and destination- wise growth rate from 2001-02 to 2016-17.To analyse the export data and arriveat appropriate results, Growth Rate analysis, Instability analysis and Markov Chain analysis were used.Theresults indicated that the export of fresh grapes with the pre-WTO and post-WTO period when compared, thegrowth rate of post-WTO period decreased in terms of quantity, value and unit value of export. However,theoverall growth rate was positive. The Netherlands, The United Kingdom, The United Arab Emirates, Bangladeshand Germany are major importers of fresh grapes from India, and these countries have a positive growth rateduring the study period. The results of the Transitional Probability Matrix of fresh grapes export from Indiashowed that The Netherlands was one of the stable markets of Indian fresh grapes as reflected by the probabilityof retention.It might be due to increasing demand for fresh grapes in that country and as a crop it was notcultivated extensively in the Netherlands. However, Germany did not continue as a loyal importer of India’sfresh grapes. It might be due to rigid competition by other countries such as the Netherlands.